Casualties of care : immigration and the politics of humanitarianism in France - Ticktin, Miriam Iris (University of California Press, 2011)
This work explores the unintended consequences of compassion in the world of immigration politics. In particular it looks at two regimes of care, humanitarianism and the movement to stop violence against women.